2015
DOI: 10.5301/ejo.5000637
|View full text |Cite
|
Sign up to set email alerts
|

Early Results of Dexamethasone Implant, Ranibizumab, and Triamcinolone in Macular Edema Due to Branch Retinal Vein Occlusion

Abstract: Although RAN was the safest among the 3 agents, DEX and IVTA reduced CMT more than RAN, while significant improvement was achieved in BCVA in all groups. All 3 agents can be effectively used in the treatment of macular edema due to BRVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Intravitreal corticosteroids is another option, particularly in situations where the cost of treatment and the monthly treatment burden of anti-VEGF therapy is too difficult for patients [124]. The most commonly used steroid drug is triamcinolone acetonide (TA), which is reported to have similar or even better short-term outcomes especially in nonischemic BRVO compared with anti-anti-VEGF drugs.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravitreal corticosteroids is another option, particularly in situations where the cost of treatment and the monthly treatment burden of anti-VEGF therapy is too difficult for patients [124]. The most commonly used steroid drug is triamcinolone acetonide (TA), which is reported to have similar or even better short-term outcomes especially in nonischemic BRVO compared with anti-anti-VEGF drugs.…”
Section: Treatmentmentioning
confidence: 99%
“…Research has demonstrated that both 3-month intravitreal injections of an anti-VEGF agent bevacizumab and two IVTA injections 2 months apart could be effective in respect to both visual and anatomical outcomes [125]. TA has much lower prices but has a higher rate of adverse events like increased intraocular pressure (IOP), cataract progression, and sterile pseudoendophthalmitis [101, 124, 126130]. The SCORE study ( n = 411) showed that the outcome of IVTA 1 mg groups is similar to IVTA 4 mg groups and can lower the rate of adverse events [131].…”
Section: Treatmentmentioning
confidence: 99%
“…Both inflammation and increased vascular endothelial growth factor (VEGF) level play important role in pathogenesis of ME secondary to RVO (4)(5)(6)(7). Laser photocoagulation, vitreoretinal surgery, intravitreal anti-VEGF and steroid injections, and various surgical techniques have been reported to be effective in treatment of ME secondary to RVO (1)(2)(3)(4)(5)(6)(7)(8).Currently, intravitreal injections are particularly preferred as first-line treatment option for ME (8). Bevacizumab, ranibizumab, and aflibercept are the 3 anti-VEGF agents used in treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab, ranibizumab, and aflibercept are the 3 anti-VEGF agents used in treatment. The first drug is used off-label; the others are approved for this purpose (2,8,(9)(10)(11)(12). In pivotal multicenter studies in which strict follow-up and treatment criteria were observed, successful treatment outcomes have been reported (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation and increased vascular endothelial growth factor (VEGF) levels both play important role in pathogenesis of ME secondary to RVO (4)(5)(6)(7). Several treatment options such as laser photocoagulation, vitreoretinal surgery, intravitreal anti-VEGF and steroid injections, as well as various surgical techniques have been reported to be effective in treatment of ME secondary to RVO (1)(2)(3)(4)(5)(6)(7)(8). Currently, intravitreal injections of anti-VEGF agents or steroids are preferred as first line treatment option for ME (8).…”
Section: Introductionmentioning
confidence: 99%